EFEKTIVITAS PERGUB NOMOR 142 TAHUN 2019 TENTANG KEWAJIBAN PENGGUNAAN KANTONG BELANJA RAMAH LINGKUNGAN PADA PUSAT PERBELANJAAN, TOKO SWALAYAN, DAN PASAR RAKYAT DALAM RANGKA PENGURANGAN PENGGUNAAN KANTONG PLASTIK DI LINDETEVES TRADE CENTER (LTC) GLODOK - Hansen Joneri; Mella Ismelina F.R. (Fakultas Hukum Universitas Tarumanagara, 2020)
This Governor Regulation does not yet provide a transition period for business actors in shopping centers and markets, as well as managers in supermarkets to ensure a transition from using single-use plastic packaging bags to more environmentally friendly packaging bags. There are no social sanctions for violators, this regulation only regulates administrative sanctions for business managers and actors who do not comply, such as reprimands, writing, forced money, license suspension, and license revocation. There is no follow-up to publishing which is subject to sanctions, such as including the names of managers or business actors who violate the website of DKI Jakarta or the mass media. This mechanism cannot work if the public does not know which business managers or actors violate it. The price of Eco-friendly Shopping Bags is not affordable so it is ineffective. The lack of replacements for plastic bags at affordable prices has actually led to the rampant smuggling of plastic bags.